PENGARUH SOSIALISASI PERPAJAKAN, SANKSI PAJAK DAN PENGETAHUAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Empiris Pada KPP Pratama Boyolali) - Riyan Sufiyanto; Alean Kistiani Hegy Suryana; Nur Asih Triatmaja; Yunita Dwi Pratiwi; Amy Wulandari (EKOBIS, 2024)
Taxes are an important factor in state financing. The Directorate General of Taxes explores various approaches to increasing public compliance with tax obligations. This study examines how taxpayer compliance increases through the implementation of tax socialization, application of tax sanctions, and taxpayer knowledge. This research was conducted on people who were registered as taxpayers at the Pratama Boyolali checkpoint. The Slovin formula was used to determine the number of samples to obtain 100 respondents who were met by chance. The analysis used is multiple linear regression analysis. The test results show that each variable of tax socialization, tax sanctions, and taxpayer knowledge partially has a positive and significant effect on taxpayer compliance. Simultaneous tests produce similar results, namely the independent variables are positively related to taxpayer compliance.